Non-Diffracting Light Wave: Fundamentals and Biomedical Applications - Ren, Yu-Xuan; He, Hongsen; Tang, Huajun; Wong, Kenneth K. Y. (Frontiers in Physics, 2021)
The light propagation in the medium normally experiences diffraction, dispersion, and scattering. It is a century-old problem to study the light propagation as the photons may attenuate and wander. We will start from the fundamental concepts of the non-diffracting beams, and examples of the non-diffracting beams include but not limited to the Bessel beam, Airy beam, Mathieu beams. We then discuss about the biomedical applications of the non-diffracting beams with a focus on the linear and nonlinear imaging, e.g., light-sheet fluorescence microscopy, two-photon fluorescence microscopy. The non-diffracting photons may provide scattering resilient imaging as well as the fast speed in the volumetric two-photon fluorescence microscopy. The non-diffracting Bessel beam and the Airy beam have been successfully demonstrated in the volumetric imaging applications with faster speed since a single 2D scan provides information in the whole volume that adopted 3D scan in a traditional laser scanning microscopy. This is an important advancement in the imaging applications with sparse sample structures, especially in neuron imaging. Moreover, the fine axial resolution can be achieved by using the self-accelerating Airy beams or the deep learning algorithms. These additional features to the existing microscopy directly realize a great advantage over the field especially for the recording of the ultrafast neuronal activities including the calcium voltage signal imaging. Nonetheless, with the illumination of dual Bessel beams at non-identical orders, the transverse resolution can also be improved by the concept of image subtraction, which would provide clearer images in the neuronal imaging.